Application of International Law to the Subjects of International Relations - Filatova, Rositsa (Media and Language, 2024)
A key topic in the implementation of international relations is the application of international law. Of essential importance are the rights or functions of the subjects of international law, as well as the dependence between them. Relations between subjects of international relations depend on international law to a large extent. The main functions, rights and obligations of subjects in international relations must be carried out according to the provisions of international law.